Пепельная земля - Конторович Александр Сергеевич (Эпицентр. Ядерная фантастика, 2011)
Экземпляры: ф.6 (20200305) / Инвентарный номер: 3400zzz / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445